2015
DOI: 10.12968/bjon.2015.24.6.328
|View full text |Cite
|
Sign up to set email alerts
|

The value of Master's degrees for registered nurses

Abstract: The value of graduates in the nursing workforce has been recognised in the move to all-graduate preparation of pre-registration nurses in England ( Nursing and Midwifery Council, 2010 ). Increasingly, after registration continuing professional development programmes for nurses are being offered at Master's level. However, there is limited evidence of the relationship between postgraduate study and improved patient outcomes. Evidence that does exist suggests that nurses who engage in postgraduate study are more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…The goal of master's level education was to develop the practice of nurses through the process of learning transfer and connecting the real world of practice with knowledge and theory (Finn et al 2010). Successful learning transfer brings about direct and indirect benefits to practice through changes in attitudes, application of knowledge, improved critical thinking and decision-making skills, confidence, ability to challenge treatment decisions, use of assessment skills and research evidence, and increased job satisfaction (Barnhill et al 2012;Clark et al 2015;Cotterill-Walker 2012;Gijbels et al 2010;Ng et al 2016;Pelletier et al 2003). Importantly, the findings of a recent systematic review and meta-analysis that examined the relationship between educational preparation and patient outcomes indicate clinically important evidence of decreased patient mortality and reduced failure to rescue when there are more nurses with higher levels of education (Liao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of master's level education was to develop the practice of nurses through the process of learning transfer and connecting the real world of practice with knowledge and theory (Finn et al 2010). Successful learning transfer brings about direct and indirect benefits to practice through changes in attitudes, application of knowledge, improved critical thinking and decision-making skills, confidence, ability to challenge treatment decisions, use of assessment skills and research evidence, and increased job satisfaction (Barnhill et al 2012;Clark et al 2015;Cotterill-Walker 2012;Gijbels et al 2010;Ng et al 2016;Pelletier et al 2003). Importantly, the findings of a recent systematic review and meta-analysis that examined the relationship between educational preparation and patient outcomes indicate clinically important evidence of decreased patient mortality and reduced failure to rescue when there are more nurses with higher levels of education (Liao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[21] Spending time on research and development seems to be considered an extravagance in a clinical setting, despite requests for graduate skills over the years. [8] However, a classical ethnography by Hansen [22] shows how clinical nurses tend to spend time on paperwork, such as documentation and preparing the ward round, on days where they have plenty of time. This is contrary to what clinical nurses claim regarding busy days, where they express a common desire to be able to spend more time with the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MSN graduates' extended knowledge on academic scholarship and advanced clinical practice can have a positive impact on patient care. [8][9][10][11][12] An observational study of 422,730 patients from 300 hospitals in nine European countries showed how a 10% increase in nurses with a postgraduate degree was associated with a decrease in inpatient death within 30 days of admission by 7%. [11] Ge and colleagues [10] performed a systematic review of quantitative studies to explore the impact of master's-graduate nurses on inpatient care in different medical specialties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] MSN graduates view their postgraduate education as an important part of being in clinical practice [12] and the direct benefits of postgraduate nursing education to improve nurses' competencies are well established. [13] The value of postgraduate education for nurses is increasingly recognized and there is growing evidence that nurses who undertake further academic education are more likely to have greater academic knowledge and competencies, [14] which may lead to greater opportunities for nurses to engage in nursing research in clinical practice. The requisition of advanced professional and research capabilities, such as advanced academic skills and subject knowledge used to perform nursing research-related tasks [15] are important factors for nurses completing a higher education degree.…”
Section: Introductionmentioning
confidence: 99%